PERSEPSI MAHASISWA PERBANKAN SYARIAH UIN KHAS JEMBER TENTANG EDUKASI INVESTASI SAHAM SYARIAH. - Putra Alif Kurniawan Akbar; Elvin Adria Saputri; Ayu Dwi Yulandari; Rini Puji Astuti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The main focus of this research is to explore how students' understanding and attitudes towards the material taught in lectures and the facilities provided by the campus, such as the Sharia Investment Gallery (GIS), are shaped. The research employs a qualitative approach with a case study design, where data was collected through in-depth interviews with a number of active students who have taken courses related to Sharia stock investments. The results of the study indicate that the majority of students have a positive perception of the importance of Sharia stock investment education. However, they consider the education they receive to be limited to theory and lacking in practical aspects. Factors influencing students' perceptions include the quality of teaching, access to digital information, and student involvement in GIS activities, which remains suboptimal. Based on these findings, the study suggests the integration of practical Sharia investment experience in lectures, enhanced collaboration with GIS, and the development of digital educational content to broaden students' literacy in Sharia capital markets